Preliminary psychometric validation of patient-reported outcomes relevant to individuals with spinal muscular atrophy and their caregivers - Maria Grazia Cattinari; Samuel Ignacio Pascual-Pascual; Mencía de Lemus; Julita Medina; María Dumont; Pablo Rebollo; Juan Francisco Vázquez-Costa (Orphanet Journal of Rare Diseases)
Abstract Background There is a need to expand the current scope of assessment tools usually applied to patients with Spinal Muscular Atrophy (SMA). This study aimed to assess the psychometric properties (reliability and discriminant validity) of a set of new patient-reported outcome measures (PROMs) called PROfuture, after analysing the performance of individual items of the questionnaires. Results Patients included in the Spanish SMA Patient-Reported Registry (RegistrAME) were invited to answer 10 questionnaires: Fatigability; Pain; Scoliosis and Contractures (S&C); Feeding (F); Breathing and Voice (B&V); Sleep and Rest (S&R); Vulnerability; Infections and Hospitalisations (I&H); Time spent in care (T); and Mobility and Independence (M&I). The diagnosis date, type of SMA, functional classification, and comorbidities were also collected. A total of 160 patients of the 330 included in RegistrAME participated in the study: mean age (SD) 18 (16.6) years, 27.5% non-sitter, 46.88% sitter, and 25.63% walker, 20.0% type 1 SMA, 51.88% type 2, and 28.12% type 3. The frequency of symptoms varied from 43.5% of patients reporting some degree of Pain to 96.3% reporting some degree of Fatigability. The reliability assessed by Cronbach’s alpha coefficient was > 0.75 for all the PROs and > 0.9 for S&C, F, B&V, T, and M&I. Regarding content validity, scores were higher (worse health status) in type 1 SMA patients than in types 2 and 3, and were also higher for non-sitter patients than for sitter and walker patients. Conclusions The ten questionnaires included in the PROfuture set were developed based on what people living with spinal muscular atrophy and their caregivers consider relevant. This preliminary study provides an initial basis to consider their potential usefulness in assessing aspects that matter to this population. The early findings are promising, however, further extensive psychometric evaluation is needed. PROfuture is a new set of patient-reported outcome measures, specifically designed by and for individuals living with spinal muscular atrophy and their caregivers. Future studies will help strengthen the evidence regarding its reliability and validity.